2009
DOI: 10.1111/j.1467-8292.2009.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Banking Market Structure, Creation and Activity of Firms: Early Evidence for Cooperatives in the Italian Case

Abstract: This paper investigates whether local differences in banking competition impact on the creation and activity of firms, with a special focus on cooperatives. The econometric analysis, implemented on a sample of firms operating in the Italian provinces during the years 1998-2003, reveals non-monotonic effects of bank market power on both firm creation and activity. With regard to the former, a bell-shaped relationship is found for both cooperative and non-cooperative firms, suggesting that a moderately concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 93 publications
2
9
0
Order By: Relevance
“…As far as other countries are concerned, using Italian data at local credit markets level in the 1990s, Bonaccorsi di Patti and Dell'Ariccia (2004) provide evidence of a bell-shaped relationship between bank market power and firm creation. A similar result is reached by Gagliardi (2009), with Italian data spanning from 1998 to 2003, and by Bergantino and Capozza (2012), for Central and Eastern European transition economies in the period 2000-2007.…”
Section: 2supporting
confidence: 73%
See 2 more Smart Citations
“…As far as other countries are concerned, using Italian data at local credit markets level in the 1990s, Bonaccorsi di Patti and Dell'Ariccia (2004) provide evidence of a bell-shaped relationship between bank market power and firm creation. A similar result is reached by Gagliardi (2009), with Italian data spanning from 1998 to 2003, and by Bergantino and Capozza (2012), for Central and Eastern European transition economies in the period 2000-2007.…”
Section: 2supporting
confidence: 73%
“…This issue, raised in the debate on the economic role of bank market structure (for some reviews we refer to Cetorelli, 2001;Agostino and Trivieri, 2010), has been addressed by few studies, mainly focusing on single country cases (e.g. Bonaccorsi di Patti and Dell 'Ariccia, 2004;Gagliardi, 2009;Rogers, 2012). Our paper extends the analysis to a multi-country setting, by using data on new firms' formation concerning 106 countries in the period 2004-2011.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Such an attitude from the banks may limit the scale of the process of creating new enterprises. On the other hand, the moderately-concentrated banking market positively affects the creation of new enterprises, as competition between banks reduces the negative phenomena (Gagliardi, 2009). The limitation of investments of financial institutions in the newly created enterprises results from the uncertainty of their future success and from the existing risk of failure (Koski, Pajarinen, 2013).…”
Section: Entrepreneurial Process and Financial Constrains As Barriers For Creating A New Companymentioning
confidence: 99%
“…These recommendations are proposed as egalitarian solutions; however, upon closer scrutiny, these alternatives often are not strong enough in isolation. Past research has shown that cooperatives flourish in contexts where they are institutionally supported by local development banks (21). Employee buy-outs require unique circumstances to originate; in particular, firms must be failing or near closure so that employees can organize to form participatory management schemes.…”
Section: Employee-ownership Schemes Versus Welfare Statesmentioning
confidence: 99%